Detection of carcinogens as mutagens in the Salmonella/microsome test: assay of 300 chemicals: discussion. - McCann, J (1976)
About 300 carcinogens and non-carcinogens of a wide variety of chemical types have been tested for mutagenicity in the simple Salmonella/microsome test. The test uses bacteria as sensitive indicators of DNA damage, and mammalian liver extracts for metabolic conversion of carcinogens to their active mutagenic forms. There is a high correlation between carcinogenicity and mutagenicity: 90% (157/175) of the carcinogens were mutagenic in the test, including almost all of the known human carcinogens that were tested. Despite the severe limitations inherent in defining non-carcinogenicity, few "non-carcinogens" showed any degree of mutagenicity [McCann et al. (1975) Proc. Nat. Acad. Sci. USA 72, 5135-5139]. In the present paper, carcinogens negative in the test andapparent false positives are discussed. We also discuss evidence that chemical carcinogens and radiation, likely to initiate most human cancer and genetic defects do so by damage to DNA. The Salmonella test can play a central role in a program of prevention: to identify mutagenic chemicals in the environment (all indications are there are many) and to aid in the development of non-mutagenic products to prevent future human exposure.